2021
DOI: 10.3390/md19120678
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Mechanisms of Fucoidans to Treat Inflammatory Diseases: A Review

Abstract: Fucoidans are sulfated heteropolysaccharides found in the cell walls of brown seaweeds (Phaeophyceae) and in some marine invertebrates. Generally, fucoidans are composed of significant amounts of L-fucose and sulfate groups, and lesser amounts of arabinose, galactose, glucose, glucuronic acid, mannose, rhamnose, and xylose. In recent years, fucoidans isolated from brown seaweeds have gained considerable attention owing to their promising bioactive properties such as antioxidant, immunomodulatory, anti-inflamma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 80 publications
0
22
0
1
Order By: Relevance
“…Evidently, the resolution of fucoidans needs additional improvement. Specific enzymatic degradation of unnecessary components of the mixture [ 91 ] or affinity chromatography based on the property of sulfated polysaccharides to bind several proteins [ 92 , 93 ] may be mentioned as the possible approaches to new fractionation procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Evidently, the resolution of fucoidans needs additional improvement. Specific enzymatic degradation of unnecessary components of the mixture [ 91 ] or affinity chromatography based on the property of sulfated polysaccharides to bind several proteins [ 92 , 93 ] may be mentioned as the possible approaches to new fractionation procedures.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that seaweed polysaccharides showed significant anti-inflammatory activities in vivo and in vitro [ 4 , 48 , 49 ]. The purified fucoidan fraction from Turbinaria ornate (38% sulfates, 0.25% TPC, and 60.4% carbohydrates, among which 86% fucose) reduced ROS and NO expression in zebrafish embryos [ 14 ], reduced an arthritic score, and paw volume of rats with Freund’s Adjuvant induced arthritis [ 13 ].…”
Section: Resultsmentioning
confidence: 99%
“…Inflammatory responses are immune responses that protect the organs from infection and tissue injury. Inflammatory responses are also associated with the pathogenesis of various diseases such as diabetes, cardiovascular diseases, obesity, arthritis, stroke, and cancer [1]. Inflammatory responses are associated with the release of inflammatory molecules such as histamine, prostaglandins, nitric oxide (NO), bradykinin, and pro-inflammatory cytokines [2].…”
Section: Introductionmentioning
confidence: 99%